PANDANGAN MURID TERHADAP GURU: 60 TAHUN PROF. DR. M. AMIN ABDULLAH - Muhammad Azhar (Profetika: Jurnal Studi Islam, 2014)
This article discusses about M. Amin Abdullah’s thought (A professor at StateIslamic University Sunan Kalijaga Yogyakarta) in the field of Islamic Studies. The methodused in this paper is biographical-reflective method because the writer was his student.The focus of the writing is the heredity of the scientific methodology and its implication inthe study of Islam in Indonesia. This article concludes several Islamic scientific hereditiesfrom M Amin Abdullah majoring on the integrative-interconnectivity concept in Islamthat tends to be spaced out, especially in the study of Islamic classics. The other thoughtis about the importance of academic attitude in the development of the future Islamicstudy. In the scientific methodology aspect, he stresses the importance of the renewal inthe Islamic contemporary study to spread the teachings on the earth as the sky heredity,sacral and transcendental, to dive the needs to answer various worldly problems that areempiric and immanent. The implication of Amin Abdullah’s thought gives newinterpretation in the contemporary Islamic scientific study that is more contextualempiricaland different from textual-normative classic Islamic study format.Key Words: integration-interconnection; scientific methodology; Islamic study.Makalah ini membahas tentang pemikiran M. Amin Abdullah (Guru BesarUIN Sunan Kalijaga Yogyakarta) dalam bidang Islamic Studies. Metode penulisan yangdigunakan dalam makalah ini adalah metode biografis-reflektif karena penulis merupakansalah seorang mantan mahasiswanya. Fokus pembahasan makalah ini adalah warisanmeteodogi keilmuan dan implikasinya dalam kajian Islam di Indonesia. Makalah inimenyimpulkan beberapa warisan keilmuan Islam dari M. Amin Abdullah umumnyabermuara pada konsep integrasi-interkoneksi keilmuan dalam Islam yang selama inicenderung berjarak, khususnya dalam warisan studi keislaman klasik. Pemikiran lainnyaadalah tentang pentingnya sikap akademis dalam pengembangan studi keislaman masadepan. Dalam aspek metodologi keilmuan, beliau menekankan pentingnya pembaharuandalam studi keislaman kontemporer untuk membumikan ajaran Islam sebagai warisanlangit, sakral dan transendental, menukik pada kebutuhan untuk menjawab berbagaipersoalan duniawi yang empiris dan imanen. Implikasi pemikiran Amin Abdullah adalahmemberikan interpretasi baru studi keilmuan Islam kontemporer yang lebih kontekstualempiris,yang berbeda dengan format studi keislaman klasik yang tekstual-normatif.Kata Kunci: Amin Abdullah, metodologi keilmuan, studi Islam.